(untitled) (Malaysian Journal of Civil Engineering, 2018)
Drill cuttings from oil exploration are recognised as a major environmental concern. Current cost-effective treatment technologies often involve sending treated products to landfill without any potential end-use thereby rendering these solutions unsustainable. There is potential for using drill cuttings comprising of oily, saline and clayey waste materials as fine aggregate replacements in structural concretes requiring characteristic compressive strength from 20-32 MPa. Research into the hydration process as well as evaluating the fresh and hardened properties of mortars incorporating synthetic drill cuttings were undertaken. Replacement of sand by synthetic drill cuttings (up to 25% by weight) produced mortar with accelerated hydration as well as reduced flow and density. In addition, the 28-day compressive strength of mortar incorporating synthetic drill cuttings decreased by up to 50%. Satisfactory strength for all sand replacement levels evaluated in mortars was still attainable for reuse of these synthetic of drill cuttings as fine aggregate replacements in structural concretes.